Uji Efektivitas Ekstrak Etanol 70% Daun Ciplukan (Physalis Angulata L.) Terhadap Penurunan Kadar Glukosa Darah Pada Tikus Putih Jantan Galur Wistar (Rattus Norvegicus) Yang Diinduksi Aloksan - Rahmani, Alyssa Nabilla Syawalia (2016)
Background: Ciplukan (Physalis angulata L.) leaf has been known to contain many compounds such as chlorogenic acid, alaidic acid, citric acid, malat acid, tannin, cryptoxantin, saponin, terpenoid, flavonoid, polyphenol, alcaloid, and steroid assumed to have anti-diabetes potency Purpose of the Research: Purpose of the research is to know effectiveness of ciplukan leaf extracted by 70% ethanol on reduction of wistar-strain male mice inducting with aloxan. Method of the Research: The research is an experimental one with pre- and posttest with controlled design. Subject of the research was extract of ciplukan (Physalis angulata L.) leaf. Twenty five wistar-strain male white mice used as test animal were divided into 5 groups, namely: group I : negative control (aquadest), group II : positive control (glibenclamide), groups III, IV, V : treated with extract of ciplukan leaf with doses of 50 mg/kg BW and 200 mg/kg BW respectively that were administered orally. Blood glucose level was measured after induction of the extract at 7th day and 11th day. Result of the Research: Result of one-way Anova statistical test at 7th day obtained p value of 0.092 and p>0.05. Then, effect of the 5 groups had insignificant difference on reduction of blood glucose. While, One-Way Anova of 11th day obtained p value of 0.005 and p<0.05. Thus, effect of the 5 groups indicated significant difference on reduction of blood glucose level. Further, paired t-test was performed to know the increase of blood glucose level at 7th day and 11th day. Then, Least Significant Difference I:II : 0.005, I:III : 0.005, I:IV : 0.007, I:V : 0.000 was conducted and p<0.005. Conclusion: Results of the research showed that 70% ethanol-extracted ciplukan (Physalis angulata L.) leaf had effect of reducing blood glucose level of wistar male white mice. Doses of 50 mg/kg BW and 200 mg/kg BW were able to reduce blood glucose level at 11th day with percentage of reduction were 22.40%, 32.35% and 13.83% respectively. The greatest effect was found with dose of 100 mg/kg BW, whereas potency of reduction compared to glibenclamide obtained percentage of dose 1 : 71.34%, dose 2 : 75.8% and dose 3: 45%.